A retrospective study of Babesia macropus associated with morbidity and mortality in eastern grey kangaroos (Macropus giganteus) and agile wallabies (Macropus agilis). Issue 2 (August 2015) - Donahoe, Shannon L.; Peacock, Christopher S.; Choo, Ace Y.L.; Cook, Roger W.; O'Donoghue, Peter; Crameri, Sandra; Vogelnest, Larry; Gordon, Anita N.; Scott, Jenni L.; Rose, Karrie
Highlights: Detailed description of novel Babesia infection causing mortality in macropods. First report of this infection in agile wallabies. Information on the geographical incidence of this disease in the eastern states of Australia. Comprehensive review of the clinical signs and pathology of the disease. Graphical Abstract: Abstract: This is a retrospective study of 38 cases of infection by Babesia macropus, associated with a syndrome of anaemia and debility in hand-reared or free-ranging juvenile eastern grey kangaroos ( Macropus giganteus ) from coastal New South Wales and south-eastern Queensland between 1995 and 2013. Infection with B.   macropus is recorded for the first time in agile wallabies ( Macropus agilis ) from far north Queensland. Animals in which B.   macropus infection was considered to be the primary cause of morbidity had marked anaemia, lethargy and neurological signs, and often died. In these cases, parasitised erythrocytes were few or undetectable in peripheral blood samples but were sequestered in large numbers within small vessels of visceral organs, particularly in the kidney and brain, associated with distinctive clusters of extraerythrocytic organisms. Initial identification of this piroplasm in peripheral blood smears and in tissue impression smears and histological sections was confirmed using transmission electron microscopy and molecular analysis. Samples of kidney, brain or blood were tested using PCR and DNA sequencing of the 18S ribosomal RNA and heat shock protein 70 gene using primers specific for piroplasms. The piroplasm detected in these samples had 100% sequence identity in the 18S rRNA region with the recently described Babesia macropus in two eastern grey kangaroos from New South Wales and Queensland, and a high degree of similarity to an unnamed Babesia sp. recently detected in three woylies ( Bettongia penicillata ogilbyi ) in Western Australia.